PROBLEM OF LETTER ARCHITECTURE COMPLETION USING A * SEARCH METHOD - Santoso, Heri (ZERO: Jurnal Sains, Matematika dan Terapan, 2018)
Problems of architecture beams or commonly called Blocks Architecture is one of the classic problems in the study of Artificial Intelligence (AI), the architectural Problems of beams can be obtained from the problems that are all around us and is one of those cases that could be problems solved by using this beam is the stack, a stack problem conditions using push and pop, one of the methods that can be used is the A * Search algorithm, A * describe the process of problem solving in which one must take any decision on any of the best stride and the use of simulation in resolving the problems of architectural beams are expected to give an idea of how the process of the settlement of these problems, simulation is an attempt to copying features, display, and a real system characteristics, the expected results of the application of the algorithm is A * this is showing the form of settlement in the simulation.